Eating catch of the day: the diet of porbeagle shark Lamna nasus (Bonnaterre 1788) based on stomach content analysis, and the interaction with trawl fisheries in the south-western Atlantic (52° S–56° S) - Belleggia, Mauro (2021)
This work examined the diet of the porbeagle shark Lamna nasus in the south-west Atlantic Ocean (SWAO, Argentina, 52° S–56° S) by analysing the stomach content information obtained by scientific observers who sampled specimens captured as by-catch on-board commercial fishing vessels from 2010 to 2020. A total of 148 fishing sites were analysed, in which the estimated catch was composed mainly of hoki Macruronus magellanicus (56.00%) and southern blue whiting Micromesistius australis (33.13%). From 413 porbeagle sharks sampled (292 females and 121 males) ranging from 71 to 241 cm total length (LT) (mean: 179.76 ± 26.74 cm), 310 (75.06%) contained food in the stomachs. The forage fish were mainly hoki M. magellanicus (23.53%) and southern blue whiting M. australis (19.05%), followed by the Patagonian sprat Sprattus fuegensis (4.48%) and nototheniids (1.4%). Cephalopods and crustaceans accounted for 10% of the diet. The estimated trophic level was 4.35. Generalized linear models revealed that the consumption of hoki M. magellanicus and southern blue whiting M. australis increased with the LT of the porbeagle shark. Moreover, smaller porbeagle sharks preyed upon both small and large teleost fish, whereas larger porbeagle sharks predated exclusively upon large fish. The diet of porbeagle shark involved interactions with fisheries as it fed upon the fish species that constituted the main catch in the analysed fishing sites, as well as the main catches of the austral trawl fisheries. The ecological role of porbeagle shark observed in the SWAO exposed implications for fisheries management from a multispecies perspective.